Hospital readiness for the provision of care to critically ill patients in Tanzania- an in-depth cross-sectional study - Karima Khalid; Carl Otto Schell; Jacquie Oliwa; Mike English; Onesmus Onyango; Jacob Mcknight; Elibariki Mkumbo; Khamis Awadh; John Maiba; Tim Baker (BMC, 2024)
Abstract Background Critical illness is a state of ill health with vital organ dysfunction, a high risk of imminent death if care is not provided and potential for reversibility. The burden of critical illness is high, especially in low- and middle-income countries. Critical care can be provided as Essential Emergency and Critical Care (EECC)- the effective, low-cost, basic care that all critically ill patients should receive in all parts of all hospitals in the world- and advanced critical care- complex, resource-intensive care usually provided in an intensive care unit. The required resources may be available in the hospital and yet not be ready in the wards for immediate use for critically ill patients. The ward readiness of these resources, although harder to evaluate, is likely more important than their availability in the hospital. This study aimed to assess the ward readiness for EECC and the hospital availability of resources for EECC and for advanced critical care in hospitals in Tanzania. Methods An in-depth, cross-sectional study was conducted in five purposively selected hospitals by visiting all wards to collect data on all the required 66 EECC and 161 advanced critical care resources. We defined hospital-availability as a resource present in the hospital and ward-readiness as a resource available, functioning, and present in the right place, time and amounts for critically ill patient care in the wards. Data were analyzed to calculate availability and readiness scores as proportions of the resources that were available at hospital level, and ready at ward level respectively. Results Availability of EECC resources in hospitals was 84% and readiness in the wards was 56%. District hospitals had lower readiness scores (less than 50%) than regional and tertiary hospitals. Equipment readiness was highest (65%) while that of guidelines lowest (3%). Availability of advanced critical care resources was 31%. Conclusion Hospitals in Tanzania lack readiness for the provision of EECC- the low-cost, life-saving care for critically ill patients. The resources for EECC were available in hospitals, but were not ready for the immediate needs of critically ill patients in the wards. To provide effective EECC to all patients, improvements are needed around the essential, low-cost resources in hospital wards that are essential for decreasing preventable deaths.